1991
DOI: 10.1002/ppul.1950110310
|View full text |Cite
|
Sign up to set email alerts
|

Medical and social factors as predictors of outcome in infant tracheostomy

Abstract: SummaryWe examined the relative impact of infant tracheostomy in comparison to. associated medical and social factors, on developmental outcome as part of a cross-sectional follow-up of 32 children. These children had no mental retardation, physical handicap, or severe neurological problems, but had a history of long-term tracheostomy in infancy, ranging from 3 to 146 months duration.Medical factors evaluated included prematurity, neurological status, severity of illness, and number of weeks hospitalized. Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For the older child who has undergone tracheostomy placement, there is often a loss of the ability to communicate verbally. Previous studies have shown that tracheostomy placement negatively affects the development of expressive language skills in children, including phonation, vocal quality and articulation [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For the older child who has undergone tracheostomy placement, there is often a loss of the ability to communicate verbally. Previous studies have shown that tracheostomy placement negatively affects the development of expressive language skills in children, including phonation, vocal quality and articulation [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of a simple relationship between functional or patient-centered outcomes and disease severity has been observed for many other conditions. [9][10][11][12] The only participant in our series with poor outcomes in physical and psychological evaluations, despite less-severe amputation, also had brain involvement. This might be an important association, because cognitive skills may have an important protective or compensatory function.…”
Section: Discussionmentioning
confidence: 93%
“…Besides the morbidity and mortality of tracheotomy, patients with history of tracheotomy in infancy are associated with lower overall language and auditory comprehension, speech developing problems and moderate to severe mental and physical impairments 25,26 . Caretakers of tracheotomized patients often score low on all aspects of quality of life including sleep, relationships, social life and ability to work 13 .…”
Section: Discussionmentioning
confidence: 99%